Platelet-activating factor-mediated transmembrane signaling in human B lymphocytes is regulated through a pertussis- and cholera toxin-sensitive pathway. - Mazer, B D (1992)
Platelet-activating factor (PAF) stimulates human B cells, resulting in elevation of intracellular calcium and the release of inositol phosphates. This signaling pathway is inhibited in the presence of pertussis (PT) or cholera toxin (CT). Preincubation of human B cells with either toxin, but not their inactive subunits, for 3 h blocked these PAF-induced responses in two B-lymphoblastoid cell lines. This effect was time dependent, with some inhibition noted at 30 min, but only after preincubation for 2-3 h was maximum inhibition achieved. This inhibitory activity was also dose dependent. The toxins blocked both PAF-induced transmembrane uptake of Ca2+ as well as release of Ca2+ from internal stores, and were selective in that activation events after cross-linking of surface IgM were not affected. Further, the toxins did not appear to act through elevation of intracellular levels of cAMP. These data, coupled with previous observations on the absence of heterologous desensitization between PAF and sIgM receptors, may delineate distinct signaling pathways in human B cells. This may reflect different roles for GTP-binding proteins in the activation of human B cells.